PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP MINAT MENGGUNAKANAPLIKASI MOBILE JKN PADA PESERTA BPJS KESEHATAN DI KLINIK PRATAMA DELIMA - Roy Purba, Roberto; Butar, Dornauli Butar; Siregar, Marupa (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
This study aims to determine the effect of promotion and service quality on the interest in using the JKN mobile application for BPJS Kesehatan participants at the Pratama Delima Clinic. The effect of promotion and service quality will be analyzed partially and simultaneously on the intention to use. The research method used is quantitative research. The data collection technique used a questionnaire which was distributed directly to BPJS Kesehatan participants at the Delima Pratama Clinic with a survey taking technique. The sample in this study were BPJS Kesehatan participants at the Delima Pratama Clinic. The analytical method used is validity test, reliability test, heteroscedasticity test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the research conducted show that the promotion variable (X1) and service quality (X2) have a significant effect on interest in using (Y). So, it can be concluded that the effect of each variable simultaneously can be seen that the calculated F value (42.746) > F table (3.10) or sig. of 0.000 <0.05. The data were statistically processed using the SPSS 26 program tools.